Glycocalyx shedding is markedly increased during the acute phase of Takotsubo cardiomyopathy. (15th September 2017) - Nguyen, Thanh H.; Liu, Saifei; Ong, Gao J.; Stafford, Irene; Frenneaux, Michael P.; Horowitz, John D.
Abstract: Background: Acute myocardial infarction (AMI) and other forms of myocardial acute oxidative stress are associated with variable "shedding" of the endothelial glycocalyx (GCS) which can be quantitated ex vivo by release into plasma of glycocalyx components such as Syndecan-1 (SD-1). Previous studies have implicated release of both catecholamines and BNP as potential accentuating factors in GCS: since these are prominent aspects of the pathogenesis of Takotsubo cardiomyopathy (TTC), we hypothesised that TTC is associated with increased GCS and the extent of GCS is predictable on the basis of NT-proBNP and catecholamine releases. Methods: SD-1 concentrations were measured in 48 TTC patients acutely and after 3 months, and compared with those in 12 healthy controls, and 17 patients with AMI. Correlations were sought between SD-1 levels markers of severity of TTC episodes in individual patients. Results: Acute SD-1 concentrations in TTC patients were elevated significantly ( p  < 0.0001, 1-way ANOVA) compared to control values. There were no significant correlations between SD-1 concentrations and any markers of severity of acute TTC episodes, such as NT-proBNP or catecholamine release. Over 3 months, SD-1 concentrations fell significantly ( p  = 0.0002) to approximately the same values as in control subjects. Conclusions: TTC is associated acutely with a marked increase in GCS. Potentially, GCS might contribute to increased coronary vascular permeability in TTC, thus dissociating development of myocardial oedema from severity of associated inflammation. Prevention of GCS represents a potential therapeutic option in TTC. Highlights: Acute Takotsubo cardiomyopathy (TTC) is associated with inflammatory shedding of the cellular glycocalyx. This might contribute to development of pulmonary oedema and pleural effusions in TTC. Prevention of glycocalyx shedding represents a potential therapeutic option in TTC.